2009
DOI: 10.1111/j.1365-2524.2009.00869.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists in under-resourced South African communities reflect on practice

Abstract: Increasing access to health services and the introduction of primary health care are the cornerstones of transforming healthcare initiatives in South Africa. Sustainability of healthcare provision in rural and under-resourced areas is secured by legislation of a year-long community service (CS) contract with graduating healthcare practitioners. This study explored how the first cohort of physiotherapists experienced their year-long CS and how they felt their undergraduate training prepared them for practice. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…[2,4,6] The students stated that being proficient in isiXhosa would have helped in HBR to minimise the verbal communication barrier. They reported that an introductory isiXhosa course in their 1st year seemed irrelevant to them at the time.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[2,4,6] The students stated that being proficient in isiXhosa would have helped in HBR to minimise the verbal communication barrier. They reported that an introductory isiXhosa course in their 1st year seemed irrelevant to them at the time.…”
Section: Discussionmentioning
confidence: 99%
“…[2,4] These communities are often situated in under-resourced areas. Experiencing the real-life context of clients is vital for students so that they will ultimately provide effective interventions and develop social responsibility.…”
mentioning
confidence: 99%
See 3 more Smart Citations